Peste des Petits Ruminants Virus Enters Caprine Endometrial Epithelial Cells via the Caveolae-Mediated Endocytosis Pathway - Yang, Bo; Qi, Xuefeng; Guo, Hui; Jia, Peilong; Chen, Shuying; Chen, Zhijie; Wang, Ting; Wang, Jingyu; Xue, Qinghong (Frontiers in Microbiology, 2018)
Peste des petits ruminants virus (PPRV) causes an acute and highly contagious disease of sheep and goats and has spread with alarming speed around the world. The pathology of Peste des petits ruminants is linked to retrogressive changes and necrotic lesions in lymphoid tissues and epithelial cells. However, the process of PPRV entry into host epithelial cells remains largely unknown. Here, we performed a comprehensive study of the entry mechanism of PPRV into caprine endometrial epithelial cells (EECs). We clearly demonstrated that PPRV internalization was inhibited by chloroquine and ammonium chloride, which elevate the pH of various organelles. However, PPRV entry was not affected by chlorpromazine and knockdown of the clathrin heavy chain in EECs. In addition, we found that the internalization of PPRV was dependent on dynamin and membrane cholesterol and was suppressed by silencing of caveolin-1. Macropinocytosis did not play a role, but phosphatidylinositol 3-kinase (PI3K) was required for PPRV internalization. Cell type and receptor-dependent differences indicated that PPRV entry into caprine fetal fibroblast cells (FFCs) occurred via a different route. Taken together, our findings demonstrate that PPRV enters EECs through a cholesterol-dependent caveolae-mediated uptake mechanism that is pH-dependent and requires dynamin and PI3K but is independent of clathrin. This potentially provides insight into the entry mechanisms of other morbilliviruses.